Virtual Environment for Design and Analysis (VEDA): Interactive and Immersive Energy Data Visualizations for Architectural Design. Issue 1 (1st May 2017) - Bartosh, Amber; Krietemeyer, Bess
Abstract : Visualizing energy-based data according to multiple perspectives and performance criteria is critical to understanding its spatiotemporal character, impacts on comfort, and meaning in the design decision-making process. This research examines how a virtual environment for design and analysis (VEDA) enhances design decision making through visualization techniques combining solar irradiation mapping with interactive virtual reality tools. A participant study investigates the ability of VEDA to create opportunities to better understand relationships between energy data and indoor environmental comfort. A discussion of the findings highlights applicability in architectural design and education, and the conclusions make recommendations for further development.